High pressure-driven effects on the structural and spectroscopic attributes of Eu3+-doped amorphous silicates - Muniz, R. F.; Guyot, Y.; Martinet, C.; de Ligny, Dominique; Medina, A. N.; Baesso, M. L. (Ceramics International, 2024)
The present study focuses on synthesizing and investigating the structure of Eu3+-doped sodium calcium silicate and calcium alumino silicate glasses under extreme high-pressure conditions. For a thorough understanding of glassy systems in extreme conditions, we conducted in-situ micro-luminescence experiments using a diamond anvil cell, reaching pressures up to 16 GPa. Hydrostatic pressure demonstrated a notable impact on luminescence, attributed to the nephelauxetic effect causing the contraction of central-ion-ligand distances. The band transitions of Eu3+ from the 5D0 to 7F1,2 states revealed pronounced pressure-induced splitting, highlighting the pressure influence on crystal-field properties. The energy shifts for the 5D0 → 7F1 transitions were determined to be 0.14 nmGPa−1 and 0.20 nmGPa−1 for sodium calcium silicate and calcium alumino silicate, respectively. These distinct slope differences indicated a lower structural adaptability of the former glass, resulting in reduced deformability under high-pressure conditions. Furthermore, as pressure increased, the asymmetry ratio of the 5D0 → 7F2/1 transitions decreased, though it consistently maintains levels higher than unity, reflecting the highly asymmetric environment surrounding Eu3+ ions. The estimated elastic limit for both samples was approximately 7 GPa. To assess pressure-induced changes in the local environment, Judd-Ofelt intensity parameters were employed for the calcium alumino silicate glass. The trends observed throughout compression revealed that Ω2 > Ω4 up to 6.8 GPa, while Ω2 < Ω4 for higher pressures, indicating higher covalency between Eu3+ ions and ligands in the elastic domain compared to the plastic domain. The observed increase in Si and Al coordination in the plastic domain was found to play a role in these parameters.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Europium probe; High pressure; Luminescence; Silicate glasses; Structure